Theatre in ancient India - Chattopadhyay, Siddheswar (New Delhi : Manohar Publications, 1993)
Essays on Sanskrit drama and dramaturgy.
Includes passages in Sanskrit (Sanskrit in roman).
Includes bibliographical references and index.
Keywords: Sanskrit drama -- History and criticism; Theater -- India -- History